Aplicación de un anticonceptivo temporal (Acetato de medroxiprogesterona) y determinación de sus efectos colaterales en hembras caninas (canis lupus familiaris) en la Clínica Veterinaria “HACHIKO - Ñato Suquillo, Julio César (2022)
The present titling work exposes the application of a temporary contraceptive (medroxyprogesterone acetate) and determination of its side effects in female dogs (canis lupus familiaris); To evaluate (medroxyprogesterone acetate) in female dogs (canis lupus familiaris) at the "HACHIKO" veterinary clinic through physiological and anatomical alterations to establish side effects of its use. Research that was carried out in the Rumiñahui canton in the city of Sangolquí at the "HACHIKO" veterinary clinic. The results obtained show that it is one of the most used and highly effective contraceptives, obtaining as a result 100% oestrus inhibition in the study cases. With the dosing of medroxyprogesterone acetate that was applied every 6 months to the 20 bitches; 11 presented the same effects at each dose, obtaining as results 25% alopecia, 20% discoloration of the inoculation point and 10% lactation (secretion and excretion of milk by the mammary glands). It is obtained as conclusions that the SINGESTAR contraceptive (medroxyprogesterone acetate) is 100% effective allowing the inhibition of estrus. Another aspect to note is that medroxyprogesterone generates side effects since with a dosage of three applications with an interval of six months, the females presented effects due to progestogens; These effects occurred from the first, second, and third doses.